Exploring the Impact of Digital Transformation on Human Resource Management: A Bibliometric Analysis of Strategic Innovation and Organizational Efficiency - Azzahra, Salwa; Pratiwi, Niken Aprilla (Indonesian Journal of Advanced Research, 2025)
This study systematically examines the evolving landscape of digital transformation in human resource management (DT-HRM) through a bibliometric analysis of literature indexed in Scopus from 2008 to 2025. The analysis reveals a significant surge in scholarly interest, particularly after the COVID-19 pandemic, reflecting a paradigm shift from conventional HR practices to data-driven and technology-based strategies. Key themes identified include artificial intelligence, digital technologies, innovation, leadership, and strategic alignment within HRM. The findings highlight the multidisciplinary and global nature of DT-HRM research, with contributions spanning diverse sectors and regions. Despite this growth, the literature remains fragmented, underscoring the need for integrative approaches that combine bibliometric and content-based analyses to deepen theoretical and practical insights. The study also emphasizes the importance of addressing ethical, cultural, and social implications of technology adoption in HR. These insights provide valuable guidance for academics, practitioners, and policymakers to foster evidence-based innovation, responsible technology implementation, and strategic alignment in HRM, ultimately enhancing organizational efficiency and adaptability in the digital era.